Design of a Knee Exoskeleton Using Foot Pressure and Knee Torque Sensors. (20th August 2015) - Kim, Jung-Hoon; Shim, Myounghoon; Ahn, Dong Hyun; Son, Byoung Jong; Kim, Suk-Young; Kim, Deog Young; Baek, Yoon Su; Cho, Baek-Kyu
This study presents the development of a modular knee exoskeleton system that supports the knee joints of hemiplegic patients. The device is designed to realize the polycentric motion of real human knees using a four-bar linkage and to minimize its total weight. In order to determine the user's intention, force-sensitive resistors (FSRs) in the user's insole, a torque sensor on the robot knee joint, and an encoder in the motor are used. The control algorithm is based on a finite state machine (FSM), where the force control, position control and virtual damping control are applied in each state. The proposed hardware design and algorithm are verified by performing experiments on the standing walking and sitting motion controls while wearing the knee exoskeleton.